Correction of multiple complex lower limb deformities by intramedullary nailing. (December 2015) - Rocca, Guido; Spina, Mauro; Carpeggiani, Guilherme; Schirru, Luigi
Abstract: A female patient presented to our institution suffering from long bone post-traumatic multiple deformities. Her walking was limited, painful and teetering. It had worsened over the past months. The right leg was shortened by 6 cm compared to the contralateral. The right femur was 18° varus, the right tibia was 16° valgus, the left tibia was 12° varus. Both knee joints showed marked radiographic signs of osteosclerosis. After a thorough study with simulations using paper models, we carried out three osteotomies, two open wedge and one cuneiform, stabilizing them with intramedullary nails. We conducted the operation in two stages, in order to avoid an excessive surgical stress that could give rise to complications such as DVT, fat embolism, and respiratory insufficiency. This allowed a rapid recovery of her weight bearing and walking capacity, reducing significantly also the leg length discrepancy. She progressed uneventfully to healing of the osteotomy sites and she returned to her previous occupation.